ANALYSIS OF THE EFFECT OF INFLATION AND EXCHANGE RATE ON EXPORTS IN 5-YEAR ASEAN COUNTRIES (YEARS 2010–2020) - Mia Amelia; Rafli Risandi; Naptania Ilmas (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
International trade is a form of economic cooperation between two or more countries that provides direct benefits. International trade has an important role because a country cannot meet all domestic needs and with international trade, every country in the world can exchange resources owned by each country, with the aim that there is no excess or lack of resources in each country in the world. This research was conducted in 5 countries in ASEAN, namely Indonesia, Singapore, Thailand, Malaysia, and the Philippines with a period being tested for 11 years starting from 2010 to 2020 with 2 independent variables being tested, namely inflation and the exchange rate in 5 ASEAN countries and the dependent variable tested is Exports in the 5 ASEAN countries. Analysis of the data used in this study is panel data regression. The results of this analysis show that inflation and exchange rates have a negative and significant effect on exports in the five ASEAN countries, which means that if inflation or the exchange rate in a country increase, exports will decrease and vice versa. So, the macroeconomic factors that exist in a country must still be considered and also considered in international trade activities.